Faecal calcium excretion does not decrease during long‐term feeding of a low‐calcium diet in adult dogs. Issue 2 (13th November 2017) - Schmitt, S.; Mack, J.; Kienzle, E.; Alexander, L. G.; Morris, P. J.; Colyer, A.; Dobenecker, B.
Summary: According to a previous meta‐analysis, adult dogs do not notably increase calcium absorption from the gastrointestinal tract when calcium intake is decreased. This results in a negative calcium balance even with a moderate calcium reduction. In this study we wanted to verify (i) whether a negative calcium balance occurs at a calcium intake equivalent to NRC (2006) (Nutrient requirements of dogs and cats, 2006, The National Academies Press, Washington, DC) minimal requirements, and if so (ii) whether the negative calcium balance will persist for up to 6 months on a low‐calcium diet. After a pre‐feeding period of at least 18 weeks with calcium intake slightly exceeding maintenance requirements (200 mg/kg body weight 0.75 ), 12 dogs (6 Beagles, 6 Foxhound crossbreds) were fed a low‐calcium diet for 28 weeks. One dog was removed from the trial for reasons unrelated to the study at week 23. Calcium intake amounted to 60 mg/kg body weight 0.75 corresponding to the minimal requirement for maintenance in dogs (NRC, 2006 (Nutrient requirements of dogs and cats, 2006, The National Academies Press, Washington, DC)). Digestion trials were carried out at week 7, 14, 21 and 28 of the low calcium feeding period. At these time points, and at week 18 of the pre‐trial, blood samples were taken and analysed for calcium, ionised calcium, phosphorus, parathyroid hormone, vitamin D, serum crosslaps and bone alkaline phosphatase. Apparent calcium digestibility was negative throughout the study, suggesting a negative calcium balance. There was no systematic decrease in faecal calcium excretion. Serum calcium, ionised calcium and phosphorus remained within the reference range. Serum crosslaps increased continuously from baseline to week 28 of trial, with averages increasing from 0.102 ng/ml to 0.279 ng/ml, suggesting osteoclastic activity, indicative of calcium mobilisation from the skeleton. The study supports the theory of a lack of adaptation of intestinal calcium absorption from diets with relatively low calcium content in dogs. This agrees with clinical findings in dogs eating low‐calcium diet.